2015
DOI: 10.1098/rspa.2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on generation of surface waves by an underwater moving bottom

Abstract: We report laboratory experiments on surface waves generated in a uniform fluid layer whose bottom undergoes an upward motion. Simultaneous measurements of the free-surface deformation and the fluid velocity field are focused on the role of the bottom kinematics (i.e. its spatio-temporal features) in wave generation. We observe that the fluid layer transfers bottom motion to the free surface as a temporal highpass filter coupled with a spatial low-pass filter. Both filter effects are often neglected in tsunami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Linear wave theory indicates that seismic displacement by stochastic source models and tsunami generation can 40 constructively interfere (Geist 2015). Jamin et al (2015) computed theoretically the kinetic energy and the free surface elevation by an underwater moving bottom using the linear water wave theory and showed that the theoretical results displayed very good agreement with the experimental data. Nonlinear effects become significant and dominant as tsunami enters the run-up phase, see (Lynett and Liu 2002;Glimsdal et al 2007;Løvholt et al 2012;Samaras et al 2015).…”
Section: Mathematical Formulation Of the Linear Water Wave Problemsupporting
confidence: 60%
See 4 more Smart Citations
“…Linear wave theory indicates that seismic displacement by stochastic source models and tsunami generation can 40 constructively interfere (Geist 2015). Jamin et al (2015) computed theoretically the kinetic energy and the free surface elevation by an underwater moving bottom using the linear water wave theory and showed that the theoretical results displayed very good agreement with the experimental data. Nonlinear effects become significant and dominant as tsunami enters the run-up phase, see (Lynett and Liu 2002;Glimsdal et al 2007;Løvholt et al 2012;Samaras et al 2015).…”
Section: Mathematical Formulation Of the Linear Water Wave Problemsupporting
confidence: 60%
“…maximum amplification, see Ramadan et al 2011). This solution is accurate if the depth of the water, h, is much greater than the amplitudes of and ζ (sea floor uplift) and η (free surface elevation) and if the wavelength of the leading wave of the incoming tsunamis is very 50 long in comparison with the local water depth, which is usually true for most tsunamis triggered by submarine earthquakes, slumps and slides, see (Todorovska and Trifunac 2001;Trifunac et al 2002;Todorovska et al 2002;Trifunac et al 2003;Hayir 2006;Jamin et al 2015). All these studies neglected the nonlinear terms in the boundary conditions to study the generation of the tsunami waves using the transform methods.…”
Section: Mathematical Formulation Of the Linear Water Wave Problemmentioning
confidence: 99%
See 3 more Smart Citations